Enduring battle : American soldiers in three wars, 1776-1945 - Hamner, Christopher H. (Modern war studies., 2011)
Hamner contrasts the experience of infantry combat on the ground in the eighteenth and nineteenth centuries, when soldiers marched shoulder-to-shoulder in linear formations, with the experiences of dispersed infantrymen of the mid-twentieth century. Earlier battlefields prized soldiers who could behave as stoic automatons; the modern dispersed battlefield required soldiers who could act autonomously. As the range and power of weapons removed enemies from view, combat became increasingly depersonalized, and soldiers became more isolated from their comrades and even imagined that the enemy was targeting them personally. What's more, battles lengthened so that exchanges of fire that lasted an hour during the Revolutionary War became round-the-clock by World War II.